ACE insertion/deletion polymorphism (rs1799752) modifies the renoprotective effect of renin-angiotensin system blockade in patients with IgA nephropathy. (September 2015) - Teranishi, Junya; Yamamoto, Ryohei; Nagasawa, Yasuyuki; Shoji, Tatsuya; Iwatani, Hirotsugu; Okada, Noriyuki; Moriyama, Toshiki; Yamauchi, Atsushi; Tsubakihara, Yoshiharu; Imai, Enyu; Rakugi, Hiromi; Isaka, Yoshitaka
Introduction: Little is known about genetic predictors that modify the renoprotective effect of renin-angiotensin system (RAS) blockade in IgA nephropathy (IgAN). Materials and methods: The present multicenter retrospective observational study examined effect modification between RAS blockade and three RAS-related gene polymorphisms in 237 IgAN patients, including ACE I/D (rs1799752), AT1R A1166C (rs5186) and AGT T704C (rs699). Results: During 9.9 ± 4.2 years of observation, 63 patients progressed to a 50% increase in serum creatinine level. Only ACE I/D predicted the outcome ( ACE DD vs ID/II, hazard ratio 1.86 (95% confidence interval 1.03, 3.33)) and modified the renoprotective effect of RAS blockade ( p for interaction between ACE DD and RAS blockade = 0.087). RAS blockade suppressed progression in ACE DD patients but not in ID/II patients ( ACE ID/II with RAS blockade as a reference; ID/II without RAS blockade 1.45 (0.72, 2.92); DD without RAS blockade 3.06 (1.39, 6.73); DD with RAS blockade 1.51 (0.54, 4.19)), which was ascertained in a model with the outcome of slope of estimated glomerular filtration rate ( p = 0.045 for interaction). Conclusion: ACE I/D predicted the IgAN progression and the renoprotective effect of RAS blockade in IgAN patients whereas neither AT1R A1166C nor AGT T704C did.